Hocus Pocus [videorecording (DVD)] - Ortega, Kenny; Midler, Bette; Parker, Sarah Jessica; Najimy, Kathy; Katz, Omri, 1976-; Birch, Thora (Disney, 2018)
After 300 years, three sister witches are resurrected in Salem, Massachusetts on Halloween night. It's up to two teenagers, a young girl, and an immortal cat to put an end to the witches' reign of terror once and for all.